If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 8) + -4whenx = 4 Reorder the terms: 5(8 + x) + -4whenx = 4 (8 * 5 + x * 5) + -4whenx = 4 (40 + 5x) + -4whenx = 4 Reorder the terms: 40 + -4ehnwx + 5x = 4 Solving 40 + -4ehnwx + 5x = 4 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -4ehnwx + -40 + 5x = 4 + -40 Reorder the terms: 40 + -40 + -4ehnwx + 5x = 4 + -40 Combine like terms: 40 + -40 = 0 0 + -4ehnwx + 5x = 4 + -40 -4ehnwx + 5x = 4 + -40 Combine like terms: 4 + -40 = -36 -4ehnwx + 5x = -36 Add '-5x' to each side of the equation. -4ehnwx + 5x + -5x = -36 + -5x Combine like terms: 5x + -5x = 0 -4ehnwx + 0 = -36 + -5x -4ehnwx = -36 + -5x Divide each side by '-4hnwx'. e = 9h-1n-1w-1x-1 + 1.25h-1n-1w-1 Simplifying e = 9h-1n-1w-1x-1 + 1.25h-1n-1w-1 Reorder the terms: e = 1.25h-1n-1w-1 + 9h-1n-1w-1x-1
| 6(5a-b)-6(7b-7a)= | | -1/99y=0 | | a/2.4=26 | | -2/5y=-14 | | 19.54+(-2.77)+0.51= | | 5x+y=54 | | x=24+3y/8 | | (7x^4+8x^3-6)-(3x^2-9x+1)= | | x=-(-24-3y)/8 | | 3600/(62.5) | | (w-2)(w)=112 | | 2x+2.2=5.8 | | 3/5x^2+2x+3/5 | | 3/5x^2 | | x^2+y^2+2x-2y-34=0 | | x=1-1 | | 2x^2-20x-6=0 | | X+0.8y=27 | | -178/4 | | 84+96+88+x=90 | | 84+96+88+x/4=90 | | 0.8x+y=27 | | x=-(72-9/8*y) | | 25n^2-70n+49=0 | | x=-72+9y/8 | | 7x+4y=75 | | 2y+13=25 | | 11x-32=22x+24 | | c/12-7=-12 | | y=72+8x/9 | | 1/40x2800 | | (3-5t)(7-8t)= |